Número completo: Vol. 4 Núm. 10 (2021): Revista RedCA (junio-septiembre 2021) - RedCA, Gestor (Revista RedCA; Vol. 4 Núm. 10 (2021): Revista RedCA (junio-septiembre 2021), 2021)
Número completo: Vol. 4 Núm. 10 (2021): Revista RedCA (junio-septiembre 2021)